Analysis of dry sliding friction and wear behaviour of AA6351–SiC–B4C composites using grey relational analysis. (December 2014) - Thirumalai Kumaran, S.; Uthayakumar, M.; Aravindan, S.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper describes the multifactor based experiments that are applied to investigate the dry sliding wear system of aluminium matrix alloy (AA6351) with 5 wt-% silicon carbide (SiC), 5 wt-% and 10 wt-% of boron carbide (B4C) reinforced metal matrix composites (MMCs). Stir casting route was adopted to prepare the composites and the tribological experiments were carried out on pin-on-disc type wear machine. The effects of parameters like applied load, sliding velocity, wt-% of B4C on the dry sliding wear and frictional coefficient of aluminium MMCs using grey relational analysis (GRA) are reported. The orthogonal array with L9 layout and analysis of variance were used to investigate the influence of the parameters. It is observed that the dry sliding friction and wear behaviour of the composites are influenced by the applied load, sliding velocity and wt-% of B4C with a contribution of 60·82%, 21·72% and 14·28% respectively. The optimal design parameters were found by grey relational grade and a good agreement was observed for 95% level of confidence.